PELAKSANAAN ORIENTASI PASIEN BARU DI RSUD PETALA BUMI PROVINSI RIAU - junia (Yayasan Pendidikan Medika Indonesia, 2020)
New patient orientation is a process of accepting new patients and their family right when the patients just arrive (the first 24 hours) and the patients’ condition is already relaxed. The results of researcher’s observation, the nurses still did conduct new patient orientation in accordance with the standard of operational procedure determined. New patient orientation aims to nurture trusting relationship and initial information related to the process of patients’ care. This research aims to see the implementation of new patient orientation at RSUD Petala Bumi Riau Province. The type of this research was quantitative with survey design. The population in this research were the nurses in inpatient rooms at RSUD Petala Bumi Riau Province. The sampling technique used was consecutive sampling and the number of samples were 35 respondents in patient rooms on RSUD Petala Bumi, Riau Province. Data collection instrument was 21 interview respondents and 14 observation respondents. Analysis used in this research was univariate analysis. The research results show that the implementation of orientation on how to use the bel is conducted (78,6%), orientation on the rules, facilities, rights and obligations are not done yet (100%), orientation of patient visiting hours (14,3%). Based on the research results, the nurses at RSUD Petala Bumi Riau Province are expected to improve the implementation of new patient orientation in line with the SOP especially about rules orientation, facilities, and rights and obligation of patients.